Short-term spinal cord stimulation in treating disorders of consciousness monitored by resting-state fMRI and qEEG: The first case report - Yang, Yi; He, Qiheng; He, Jianghong (Frontiers in Neurology, 2022)
Disorders of consciousness (DOC) is one of the most frequent complications in patients after severe brain injury, mainly caused by trauma, stroke, and anoxia. With the development of neuromodulation techniques, novel therapies including deep brain stimulation (DBS) and spinal cord stimulation (SCS) have been employed to treat DOC. Here, we report the case of a DOC patient receiving short-term SCS (st-SCS) treatment and showed improvement monitored by resting-state fMRI (rs-fMRI) and quantitative EEG (qEEG). A 35-year-old male patient, suffering from severe traumatic brain injury and fell into the coma for 3 months. The patient was evaluated using JFK coma recovery scale – revised (CRS-R) and showed no improvement within 1 month. He received st-SCS surgery 93 days after the injury and the stimulation was applied the day after surgery. He regained communication according to instructions on day 21 after surgery and improved from vegetative state/unwakefulness syndrome to emergence from minimally conscious state. To our knowledge, this report is the first published case of st-SCS in a patient with DOC. These results shed light on that st-SCS may potential be an effective way of treatment for certain patients with DOC, which may reduce patients’ suffering during treatment and release the financial burden.